2020
DOI: 10.1155/2020/1378086
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Strategy of Chrysichthys nigrodigitatus (Lacepede, 1803) in a Natural Environment in the Nkam River, Littoral Cameroon

Abstract: A study on the reproductive strategy of Chrysichthys nigrodigitatus was conducted from October 2015 to August 2016, in the Nkam River in Yabassi, Littoral Region of Cameroon. For this purpose, 154 specimens of C. nigrodigitatus with total mean weight of 829.96 ± 829.58 g and total mean length of 367 ± 156 mm collected from artisanal fishermen were used. Twenty-nine (29) females at stage V of sexual maturity were selected for the evaluation of the fecundity. It appears that the oogenesis in C. nigrodigitatus is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…4 showed that fishing occurred more during the rainy season from April to September, representing 86.67% of the fishermen. This is in agreement with the reproductive cycle of the fish, making it more abundant and available for fishing during the rainy season (Ezenwa 1981;Adite et al 2017;Tiogue et al 2020). Thus, fishermen exploit its vulnerability during the season which coincides with the breeding season.…”
Section: Fishing Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…4 showed that fishing occurred more during the rainy season from April to September, representing 86.67% of the fishermen. This is in agreement with the reproductive cycle of the fish, making it more abundant and available for fishing during the rainy season (Ezenwa 1981;Adite et al 2017;Tiogue et al 2020). Thus, fishermen exploit its vulnerability during the season which coincides with the breeding season.…”
Section: Fishing Methodssupporting
confidence: 83%
“…However, 50% of the respondent's fish throughout the year while another 50% only fish during the rainy season. The opinion of the fishermen appears to agree with the findings of Ekanem (2000), Offem et al (2008), andTiogue et al (2020) which confirmed the peak breeding period observed between April and June in Rivers in Nigeria and Cameroun. The species is therefore not a particular target during the dry season but undertakes short migration for breeding during the rainy season.…”
Section: Biological Condition and Characteristics Of Pairs In Drumssupporting
confidence: 84%
“…The K factors obtained in this study could be compared favourably with reports for different fish species in water bodies in parts of Africa including Cameroon. Lower K factor values were obtained for Alien Fish Species (0.70 ± 0.40) in the Mbô Floodplain Rivers in Cameroon [62,63],' Chrysichthys nigrodigitatus (1.07 ± 0.09) in the Nkam River, Littoral Cameroon (Tiogué et al, 2020), C. auratus (1.0 to 2.9) in River Benin Nigeria [64]; Chrysichthys auratus auratus (1.136 and 1.066) and C. auratus longifilis (1.137 and 1.016) in El-Nozha Hydrodrome [65], male C. auratus (1.87 ± 0.08) in Aiba Reservoir, Nigeria [66] and Coptodon zillii (1.32), Synodontis schall (1.63) and Chrysichthys nigrodigitatus (0.97) in Lake Taabo [67]. However, higher or comparable K factor values were observed for 22 fresh water fish species (0.884±0.085 to 8.968±1.818) in the Solomougou Dam Lake, Korhogo, Côte d'Ivoire [68].…”
Section: Discussionmentioning
confidence: 83%
“…Condition factor of fish are affected by Regional water variations due to environmental conditions and availability of feeds as well as the strain, species, stress and sex of the fish [63,40,31,66,69]. Also, the physicochemical parameters of water may influence the vertical and horizontal migration of fishes in aquatic ecosystem, their distribution, feeding patterns and wellbeing [70][71][72][73][74][75][76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…This study however compared favorably with Akombo et al 18 and Taiwo and Odunaiya 19 where almost equal proportions of male and female numbers of these species were observed even though their abundance was in favour of female specimens. The biological status of the aquatic environment largely depends on the physiological condition, dynamics of various life stages, productivity and growth patterns 20 . This makes having information on fish stock assessment ultimately very important.…”
Section: Discussionmentioning
confidence: 99%